(untitled) (International Journal of Ayurveda and Pharma Research, 2020)
Owing to wide range of medicinal properties, Nirgundi is very useful herb. It is used for its medicinal values for thousands of years by the people all over the globe. The folklore healers use the plant for various ailments. As per Ayurvedic system of medicine, its Rasa is Katu, Tikta and Kashaya and it pacifies Vata and Shleshma. Its property is Laghu and Veerya is Sheetoshna and is used in the treatment of various disorders like Pleeha rog, Gulma, Krimi, Kushtha, Vrana, Visha and Aruchi. Available ancient and modern contemporary literature has been studied thoroughly while preparing this article so as to put all the available knowledge about the herb at one place. Various properties possessed by the plant have been evaluated in different studies, and results or observations of few of such prominent studies have been presented here to enrich the knowledge. Review of the available literature showed that it possesses various pharmacological activities cardiotonic, anti-inflammatory, analgesic, anti-histaminic, anti-cancerous, anxiolytic, anti-asthmatic, hepatoprotective etc. All these properties have been authenticated by various experimental and clinical studies. So keeping in view the huge potential of the plant, further research is suggested to extract maximum benefits for the benefit of the society.